Integrated system approach to dark fermentative biohydrogen production for enhanced yield, energy efficiency and substrate recovery - Sekoai, Patrick T.; Yoro, Kelvin O.; Bodunrin, Michael O.; Ayeni, Augustine O.; Daramola, Michael O. (Reviews in environmental science and biotechnology, 2018)
The challenges of climate change, dwindling fossil reserves, and environmental pollution have fuelled the need to search for clean and sustainable energy resources. The process of biohydrogen has been highlighted as a propitious alternative energy of the future because it has many socio-economic benefits such as non-polluting features, the ability to use diverse feedstocks including waste materials, the process uses various microorganisms, and it is the simplest method of producing hydrogen. However, the establishment of a biohydrogen driven economy has been hindered by low process yields due to the accumulation of inhibitory products. Over the past few years, various optimization methods have been used in literature. Among these, integration of bioprocesses is gaining increasing prominence as an effective approach that could be used to achieve a theoretical yield of 4 mol H 2 mol −1 glucose. In batch integrated systems, dark fermentation is used as a primary process for conversion of substrates into biohydrogen, carbon dioxide, and volatile fatty acids. This is followed by a secondary anaerobic process for further biohydrogen conversion efficiency. This review discusses the current challenges facing scale-up studies in dark fermentation process. It elucidates the potential of batch integrated systems in biohydrogen process development. Furthermore, it explores the various integrated fermentation techniques that are employed in biohydrogen process development. Finally, the review concludes with recommendations on improvement of these integrated processes for enhanced biohydrogen yields which could pave a way for the establishment of a large-scale biohydrogen production process.